CORRELATION OF SERUM POTASSIUM LEVEL WITH CHRONIC KIDNEY DISEASE(STAGE IV &V)-AN OBSERVATIONAL STUDY. - DR.RATHIROOPAVATHY,; DR. A.J.MANJULA DEVI,; DR. KALAI SELVI.V, (International Journal of Pharma and Bio Sciences, 2014)
Hyperkalemia with Chronic kidney disease(CKD) has possible implications for associated adverse cardiac outcomes. The present study was planned to evaluate the serum potassium levels and correlate them with glomerular filtration rate(GFR) in patients of CKD.The occurrence of hyperkalemia increase with CKD and increase the odds of mortality.